Percutaneous closure versus surgical repair for ruptured sinus of valsalva aneurysm: A systematic review and meta-analysis - Mao, Yong; Wang, Cingting; Li, Yongnan; Guan, Xinqiang; Zhang, Xiaopeng; Wu, Xiangyang (Frontiers in Cardiovascular Medicine, 2023)
Objectives: Ruptured sinus of Valsalva aneurysm (RSVA) often has an abrupt onset, and can chest pain, acute heart failure, and even sudden death. The effectiveness of different treatment modalities remains controversial. Thus, we completed a meta-analysis to evaluate the efficiency and safety of traditional surgery vs percutaneous closure (PC) for RSVA. Methods： We carried out a meta-analysis using PubMed, Embase, Web of Science, Cochrane Library, China National Knowledge Infrastructure (CNKI), WanFang Data, and the China Science and Technology Journal Database. The primary outcome was comparing in-hospital mortality between the two procedures, and the secondary outcome was documenting postoperative residual shunts, postoperative aortic regurgitation, and length of hospital stay in the two groups. Differences were expressed as odds ratios (ORs) with 95% confidence intervals (CIs) to assess the relationships between predefined surgical variables and clinical outcomes. This meta-analysis was conducted using Review Manager software (version 5.3). Results: The final qualifying studies included 330 patients from 10 trials (123 in the percutaneous closure group, and 207 in the surgical repair group). When PC was compared to surgical repair, there were no statistically significant differences in in-hospital mortality (overall OR: 0.47, 95%CI 0.05–4.31, P = 0.50). However, percutaneous closure did significantly decrease the average length of hospital stay (OR: -2.13, 95% CI -3.05 to -1.20, P＜0.00001) when compared to surgical repair, but there were no significant between-group differences in the rates of postoperative residual shunts (overall OR: 1.54, 95%CI 0.55–4.34, P = 0.41) or postoperative aortic regurgitation (overall OR: 1.54, 95%CI 0.51–4.68, P = 0.45). Conclusion: PC may become a valuable alternative to surgical repair for RSVA.